Attitude of women and their husbands regarding prenatal invasive testing attending genetic clinic at a tertiary referral center, India - Koirala, Namu; Kafle, Shyam P. (Birat Journal of Health Sciences, 2020)
Introduction: Prenatal Invasive Tests (amniocentesis and chorionic villous sampling) are used during pregnancy for detection of genetic anomalies. Due to the fear of fetal loss or various other reasons, the couples who seek to avail these tests areusually in dilemma though the chances of fetal loss following the invasive tests are very minimal. Objectives: To assess the attitude ofhigh-risk pregnantwomen and their husbands regarding the prenatal invasive tests who are referred to the genetic clinic of a tertiary referral center in India. Methodology: A descriptive, cross sectionalstudy was undertaken in 60 pregnantwomen who came to genetic clinic at a tertiary referral center in Indiafor counseling on the prenatal invasive testing. Conveniencesampling technique was used. Data was collected using a self-developed, validated semi structured questionnaire. There were total 14 items in the questionnaire where the response “Yes” was given score 3, “Uncertain/did not think about it” was given score 2 and “No” was given score 1. Maximum score was 42 and minimum was 14. The subjects were contacted by the principal investigator after the counseling for test was done by the trained counselor. The questionnaire was also administered separately to 49 accompanying husbands to assess their attitude regarding the tests. Mean, percentage, standard deviation, range and Pearson’s correlation were calculated.SPSS 16.0 version was used for data analysis. Results: Almost half of the women reported that they had adequate information regarding the test following counselling. Both the women and their husbands had unfavorable attitude towards the tests i.e. 21.98 ± 5.44 and 22.27 ± 5.11 respectively despite adequate information following counselling. The main reasons for declining the tests were fear of identification of birth defects, fear of termination of pregnancy and influence by other family membersother than their husbands. There was a significant positive correlation between the attitude of women and their husbands towards declining the prenatal invasive tests (r=0.973) at p<0.05. Conclusion: The pregnant women as well as their husbands had unfavorable attitudes towards prenatal invasive tests despite adequate information following counsellingsuggesting congruency indecision makingregarding the invasive tests.